2408: Sleep apnea is associated with increased risk for sudden unexpected death in epilepsy (SUDEP). Issue 1 (10th May 2018) - Chahal, Anwar A.; Luu, Thao; Timm, Paul; Sheppard, Paul; Sandness, David; Enke, Ashley; Dueffer, Lucas; Dresow, Max; McCarter, Stuart J.; Somers, Virend K.; Louis, Erik K. St.
Abstract : OBJECTIVES/SPECIFIC AIMS: To assess the association between probable OSA and the sudden unexpected death in epilepsy (SUDEP-7) risk profiling index in monitored adult inpatients with epilepsy. METHODS/STUDY POPULATION: We analyzed 49 consecutive adults (>18 years) with refractory epilepsy admitted to our inpatient epilepsy monitoring unit. The SUDEP-7 inventory was performed for all subjects. Probable OSA was identified using overnight oximetry, the Sleep Apnea Sleep Disorder Questionnaire (SA-SDQ), and STOP-BANG inventory. RESULTS/ANTICIPATED RESULTS: Thirty-nine percent of participants screened positive for probable sleep apnea. Patients with high SUDEP-7 scores were more likely to have a positive screen for OSA. DISCUSSION/SIGNIFICANCE OF IMPACT: OSA is an independent risk factor for sudden cardiac death. OSA may be a hitherto unrecognized contributor to sudden death risk in epilepsy. Further studies determining the relationship between OSA, neural circulatory control and SUDEP are warranted.